Jóvenes y socialización: entre el aprendizaje y el entretenimiento - Quiroz Velasco, María Teresa (2008)
The text presents an overview on the proximities and distances between knowledge and entertainment in the lives of youngsters. Internet is taken as a space for communication and for relashionships and identities re-defi nition, profi ting from an empirical research study on Peruvian youngsters.